The Potential Role of Enhanced Bond Structures in Forest Climate Finance - World Bank (Washington, DC, 2017)
This report develops innovative bond structures that respond to challenges currently limiting the financing of forest-based NDC activities, with the intention to catalyze significant increases in financing flows. The report sets out a detailed shortlist of three potential enhanced bond structures, which have the potential to catalyze funding across the gamut of forest-based nationally determined contribution (NDC) activities. The focus is on bond structures that blend donor-funded performance-based payments (PBP) alongside some upfront grant funding to improve the financial performance of the use of proceeds for issuers, and hence enable larger-scale financing from capital markets.